2020
DOI: 10.3389/fimmu.2020.01715
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Signature in Human Monocytes and Resistance to Infection in C. elegans During Fumarate-Induced Innate Immune Training

Abstract: Monocytes can develop immunological memory, a functional characteristic widely recognized as innate immune training, to distinguish it from memory in adaptive immune cells. Upon a secondary immune challenge, either homologous or heterologous, trained monocytes/macrophages exhibit a more robust production of pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, than untrained monocytes. Candida albicans, β-glucan, and BCG are all inducers of monocyte training and recent metabolic profiling analyses have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Mitochondrial dynamics is linked to mitochondrial and whole-cell homeostasis [ 45 ]; mitochondrial fission promotes mitochondrial biogenesis and allows damaged mitochondria to be excluded from the rest of the mitochondrial network, whereas mitochondrial fusion allows proteins and mtDNA exchange among mitochondria [ 29 ]. As previously shown, fumarate-exposure induces mitochondria to become more elongated, branched, and interconnected [ 35 ], which are all characteristics of mitochondrial fusion and enhanced oxidative phosphorylation [ 46 , 47 , 48 ]. Fumarate-exposure also increased both mitochondrial surface area, which may be an indicator of mitochondrial biogenesis [ 49 ], and closeness of mitochondrial cristae, which is tightly linked to mitochondrial bioenergetics, since mitochondria cristae contain the respiratory chain’s super complexes that can constantly change their arrangement and density, coordinating the kinetics of their biochemical reactions [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dynamics is linked to mitochondrial and whole-cell homeostasis [ 45 ]; mitochondrial fission promotes mitochondrial biogenesis and allows damaged mitochondria to be excluded from the rest of the mitochondrial network, whereas mitochondrial fusion allows proteins and mtDNA exchange among mitochondria [ 29 ]. As previously shown, fumarate-exposure induces mitochondria to become more elongated, branched, and interconnected [ 35 ], which are all characteristics of mitochondrial fusion and enhanced oxidative phosphorylation [ 46 , 47 , 48 ]. Fumarate-exposure also increased both mitochondrial surface area, which may be an indicator of mitochondrial biogenesis [ 49 ], and closeness of mitochondrial cristae, which is tightly linked to mitochondrial bioenergetics, since mitochondria cristae contain the respiratory chain’s super complexes that can constantly change their arrangement and density, coordinating the kinetics of their biochemical reactions [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that monocyte exposure to fumarate induces mitochondrial Ca 2+ uptake, induces mitochondrial fusion, increases Δψm, and induces mitochondrial cristae to become closer to each other, suggesting that mitochondrial activation might play a key role in fumarate-induced innate immune training [ 6 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune memory is a defining characteristic of adaptive immunity, but in recent years, evidences have demonstrated that innate immune system can display characteristics of immunological memory, termed “innate immune memory” or “trained immunity” ( 12 14 ). Bovis bacillus Calmette-Guerin (BCG), Candida albicans, Candida albicans-derived beta-glucan, and oxidized low-density lipoprotein (oxLDL) have successfully induced innate immune training of macrophages ( 41 43 ). Trained monocytes/macrophages showed the increase in the production of pro-inflammatory cytokines following re-stimulation with LPS ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through mtDNA and mitochondrial MAVS, mitochondria generate a dynamic "network" capable of expression and signaling leading to activation of immunological factors, including pro-inflammatory cytokines, e.g. type I IFN, which currently includes not only IFN-α and β, but also δ, ε, κ, θ, ω, λ, τ, ζ and ν -important elements of natural immunity, but also in the process of apoptosis and efferocytosis (Bandurska et al, 2014;Chelombitko et al, 2020;Choi et al, 2020;Cloonan and Choi, 2013;Crouse et al, 2015;Pérez-Hernández et al, 2020;Reczek & Chandel, 2015;Ren et al, 2020). It has also been shown that under physiological and pathological conditions, including viral infections, the constant cleavage and fusion of a number of kinetic proteins in the cell is dependent on the dynamic balance of the mitochondrial network.…”
mentioning
confidence: 99%
“…In the case of mice with a mutation in the mitochondrial gamma polymerase gene, a decrease in their viability was recorded (Tokarz & Blasiak, 2014). Moreover, studies conducted (Pérez-Hernández et al, 2020) on mitochondria during initial stage of innate immunity with participation of fumarate, a mitochondrial metabolite, had shown that its use caused an immediate effect of mitochondrial activation both in the human monocytes and in the organism of C. elegans, which was accompanied by their fusion, polarization and the approach of intra-mitochondrial folds, as well as the influx of calcium into the cytoplasm. Moreover, in the case of C. elegans, mitochondrial fusion in these animals was accompanied by an increase in resistance to an Escherichia coli infection (Pérez-Hernández et al, 2020).…”
mentioning
confidence: 99%